2009
DOI: 10.1194/jlr.m800666-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid 2-hydroxylase regulates cAMP-induced cell cycle exit in D6P2T Schwannoma cells

Abstract: Sphingolipids are ubiquitous components of eukaryotic cells that regulate various cellular functions. In many cell types, a fraction of sphingolipids contain 2-hydroxy fatty acids, produced by fatty acid 2-hydroxylase (FA2H), as the N-acyl chain of ceramide [hydroxyl fatty acid (hFA)-sphingolipids]. FA2H is highly expressed in myelin-forming cells of the nervous system and in epidermal keratinocytes. While hFA-sphingolipids are thought to enhance the physical stability of specialized membranes produced by thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…The fatty acid was catalyzed by fatty acid 2-hydroxylase and converted to 2-hydroxy fatty acid (hFA) and then incorporated into hFAceramide and complex hFA-sphingolipids [45]. A recent study showed that upregulation of fatty acid 2-hydroxylase could inhibit dibutyryl-cAMP-induced cell cycle exit in D6P2T Schwannoma cells [46]. The higher levels of hFA-sphingolipids indicate a higher expression level of fatty acid 2-hydroxylase, which may affect cancer cell growth in breast cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…The fatty acid was catalyzed by fatty acid 2-hydroxylase and converted to 2-hydroxy fatty acid (hFA) and then incorporated into hFAceramide and complex hFA-sphingolipids [45]. A recent study showed that upregulation of fatty acid 2-hydroxylase could inhibit dibutyryl-cAMP-induced cell cycle exit in D6P2T Schwannoma cells [46]. The higher levels of hFA-sphingolipids indicate a higher expression level of fatty acid 2-hydroxylase, which may affect cancer cell growth in breast cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…It is of interest to note that cultured rat cortical neurons showed robust, but transient, upregulation of Fa2h expression during differentiation (our unpublished data). We previously showed that FA2H modulates the cAMP signaling pathway in Schwannoma cells (Alderson and Hama 2009). It is conceivable that an FA2H-dependent regulatory mechanism for cAMP signaling exists in differentiating neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the level of upregulation was an order of magnitude greater compared to other myelin-associated genes Cgt and P 0 , suggesting that FA2H may have an additional function other than producing myelin lipids. A subsequent study of D6P2T schwannoma cells showed evidence for a role of FA2H in cell differentiation (Alderson and Hama, 2009). As Schwann cells, D6P2T cells respond to cAMP and show differentiated phenotypes, including withdrawal from the cell cycle and upregulation of myelin basic protein (Clark et al, 1998; Friessen et al, 1997).…”
Section: Hydroxy-ceramide In Cell Signalingmentioning
confidence: 99%